Erosion Process of Multiple Debris Flow Surges Caused by Check Dam Removal: An Experimental Study. Issue 3 (25th February 2022) - Wang, Xi'an; Chen, Jiangang; Chen, Huayong; Chen, Xiaoqing; Li, Shuai; Zhao, Wanyu
Abstract: Debris flows are one of the most serious natural disasters on Earth and cause great losses in human life and property each year. Check dams have been widely utilized in debris flow hazard mitigation, and over time, some control projects have exceeded their designed service lifetime. However, the processes of stored sediment erosion with multiple surges of debris flows after check dam removal are unknown. Here, the stored sediment erosion processes associated with different reductions in the dam height (i.e., the removed height) were revealed by physical experiments. The results showed that erosion was concentrated on the stored sediment scarp formed by dam removal and that the erosion process mainly included undercutting and widening. The erosion efficiency of the debris flow gradually decreased with the development of erosion and was positively correlated with removed height, negatively correlated with the accumulated debris flow volume, and proportional to the remaining potential volume of sediment to be eroded. The erosion volume development process was well described by an exponential function model, and the physical meanings of the parameters in the model and their empirical values were clarified. Moreover, the distribution of the erosion volume along the flume was shown to satisfy the Weibull distribution, and the distribution parameters were related to the removed height, erosion volume, and sediment volume fraction of the debris flow. We anticipate that our results will serve as a starting point for the demolition and reconstruction of debris flow hazard mitigation engineering in mountainous areas. Key Points: The evolution of the stored sediment landform and debris flow erosion efficiency were revealed The erosion volume development process was clarified, and its calculation formula was established The distribution characteristics of the erosion volume along the flume were described by the Weibull distribution